2010
DOI: 10.1667/rr2190.1
|View full text |Cite
|
Sign up to set email alerts
|

The Radiosensitivity of Satellite Cells: Cell Cycle Regulation, Apoptosis and Oxidative Stress

Abstract: Skeletal muscles are the organ of movement, and their growth, regeneration and maintenance are dependent in large part on a population of myogenic stem cells known as satellite cells. Skeletal muscles and these resident myogenic stem cells (i.e., satellite cells) are commonly exposed to significant doses of radiation during diagnostic procedures and/or during the radiotherapeutic management of cancer. The main objective of this study was to examine the effects of clinically relevant doses of γ radiation on sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
2
18
0
3
Order By: Relevance
“…As noted above, we recently observed that γ radiation reduces NO levels in satellite cells (20). This observation combined with those of Anderson (21) and Allen and colleagues (2225, 3133) suggests that the impaired proliferation in irradiated satellite cells might be amenable to rescue by manipulation of NO levels through pharmacological or mechanotransduced interventions.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…As noted above, we recently observed that γ radiation reduces NO levels in satellite cells (20). This observation combined with those of Anderson (21) and Allen and colleagues (2225, 3133) suggests that the impaired proliferation in irradiated satellite cells might be amenable to rescue by manipulation of NO levels through pharmacological or mechanotransduced interventions.…”
Section: Discussionsupporting
confidence: 52%
“…Unlike these overt forms of injury, irradiation of skeletal muscle elicits more subtle effects that can impair the impressive regenerative capacity of skeletal muscle by adversely impacting the activation and proliferation of satellite cells. In this context, we observed previously (20) that clinically relevant doses of γ radiation produced significant reductions in satellite cell proliferation. We also observed that γ radiation of satellite cells produced a reduction in their NO levels.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, acutely, radiation prevents mitosis of progenitor myosatellite cells (16), disrupts cell membrane permeability and lipid fluidity, and can result in sodium-potassium pump failure at the neuromuscular junction (17). Additionally, in the long-term, post-radiation inflammation, mediated by the transforming growth factor-β family, may prevent muscle growth (18), radiation-induced vascular and parenchymal damage may interfere with muscle nutrition (19), and mantle radiation may result in nemaline myopathy (20), potentially contributing to muscular atrophy (21–26), fibrosis (25–27), and hypoplasia (28).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the potential benefits of fractionation, lower radiation doses that are more clinically relevant can also impair skeletal muscle development26 and increase indices of muscle remodeling 27. Altered muscle plasticity following radiation exposure has been attributed to impaired satellite cell activity 26,28,29. Satellite cell and myoblast proliferation are reduced with as little as 2 Gy radiation exposure 2830.…”
Section: Introductionmentioning
confidence: 99%